1984
DOI: 10.1210/endo-115-1-261
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile Secretion of Luteinizing Hormone during the Menstrual Cycle of Rhesus Macaques*

Abstract: The secretion of LH, PRL, and cortisol was investigated in 4 sexually mature female rhesus macaques with cardiac catheters protected by tethers. Based on endocrine parameters, all 4 of the animals ovulated within 2 months from the time they were tethered, and regular menstrual cycles of 24-34 days were observed. The catheters remained patent for 6-12 months without reposition or repair. Plasma levels of 2 stress-labile hormones, PRL and cortisol, showed diurnal fluctuations comparable to those observed in unte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…Open bars, controls. *Significant difference between groups, P ϭ 0.02; †significant difference from before WSD, P Ͻ 0.05; #trend toward difference from before WSD, P ϭ 0.062. ular phase (38,64). Thus, it appears that, although T treatment led to an earlier activation of the LH pulse generator in monkeys (59), this difference was not maintained as monkeys matured into adulthood, and was not exacerbated by consuming a WSD.…”
Section: Discussionmentioning
confidence: 99%
“…Open bars, controls. *Significant difference between groups, P ϭ 0.02; †significant difference from before WSD, P Ͻ 0.05; #trend toward difference from before WSD, P ϭ 0.062. ular phase (38,64). Thus, it appears that, although T treatment led to an earlier activation of the LH pulse generator in monkeys (59), this difference was not maintained as monkeys matured into adulthood, and was not exacerbated by consuming a WSD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the rising tide of estrogen during the f llicular phase of the cycle is not accompanied by a reduct on in LH pulse frequency. On the contrary, it has been s ggested that the time of the initiation of the preovulatory g nadotropin surge may be associated with a small increase i the frequency of LH secretory episodes (3)(4)(5)(6)8). These servations dictate the conclusion that estrogens have little cr no effect on the modulation of LH pulse frequency, in ontrast to progesterone, which unambiguously decelerates t ie pulsatile release of this gonadotropic hormone (1-6, 8, 10, 1).…”
Section: Bstractmentioning
confidence: 99%
“…tiHely constant in the face of widely varying levels of estradiol ( 2) in the peripheral circulation-e.g., in the course of the f Ilicular phase of the menstrual cycle and after ovariectomy. MATERIALS he frequency of luteinizing hormone (LH) pulses during the f llicular phase of the menstrual cycle in women (1-6) and rhesus monkeys (7,8) does not appear to differ from that o served in the total absence of ovarian estrogen secretion ( 2, 9). Furthermore, the rising tide of estrogen during the f llicular phase of the cycle is not accompanied by a reduct on in LH pulse frequency.…”
mentioning
confidence: 99%
“…Inhibin activity in ovarian venous plasma also increases significantly at the end of gestation in the rat (12). Thus, in addition to the ovarian steroidinduced restraint on LH pulse amplitude between Days 21 and 22 of gestation, other ovarian factors found in follicular fluid may be the follicular phase of the menstrual cycle in the ovary-intact animal (32,33) and in the OVX monkey in the absence of ovarian E, (34). However, Knobil and colleagues (27) have shown that physiological follicular phase plasma levels of E, markedly reduced or completely inhibited the frequency of LH pulses in OVX monkeys.…”
Section: Discussionmentioning
confidence: 99%